PERAN PENYULUH TERHADAP IMPLEMENTASI PENGELOLAAN OPT DALAM RANGKA KEBERLANJUTAN EKOSISTEM PERTANIAN SERTA KAITANNYA DENGAN PRODUKTIVITAS PADI SAWAH DI KABUPATEN ASAHAN - Eryanto, Oktoni; Kuswardani, Retno Astuti; Noer, Zulheri; Aulia, Muhammad Reza (Fakultas Pertanian, Universitas Janabadra, 2023)
A study of the role of extension workers in the implementation of OPT management in the context of sustainable agricultural ecosystems and its relation to lowland rice productivity in Asahan Regency is very relevant to carry out. Analyzing the impact of the role of extension workers on the use of different pest management techniques in encouraging the adoption of sustainable practices will provide valuable insights for the development of more sustainable agriculture, reducing environmental and health risks, and increasing farmer productivity and welfare. The research method used is